Global Trends in Design Thinking Research in Education: A Bibliometric Analysis with Implications for Islamic Education (2015–2025) - Kustiarini; Sarwi; Rusilowati, Ani; Ratna Dewi, Novi (Universitas Muhammadiyah Magelang, 2026)
This study aims to map global research trends in Design Thinking in education and examine their implications for Islamic education using a bibliometric approach. A total of 511 Scopus-indexed journal articles published between 2015 and 2025 were analyzed using VOSviewer. The analysis examined publication trends, co-authorship networks, citation networks, international collaboration, and keyword co-occurrence. The findings indicate a substantial increase in Design Thinking publications after 2018, reaching a peak in 2023. Despite this growth, scholarly collaboration remains fragmented, with only a small proportion of authors participating in interconnected research networks. The journal Sustainability emerged as the leading publication source, while international research collaboration remained concentrated in Global North countries.Keyword analysis identified seven thematic clusters, revealing a shift from empathy- and cognition-oriented studies toward collaborative pedagogy, digital learning, and educational innovation. These findings suggest that Design Thinking has evolved into a pedagogical approach that supports learner-centered and value-based education. For Islamic education, these findings provide conceptual insights into strengthening collaboration, problem-solving, character education, and social responsibility through innovative learning practices. This study provides a comprehensive bibliometric mapping that may serve as a reference for future research and for the contextual development of Design Thinking in Islamic education